2019
DOI: 10.1155/2019/6159793
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cumulative Live Birth Rate per Total Number of Embryos to Calculate the Success of IVF in Consecutive IVF Cycles in Women Aged ≥35 Years

Abstract: Objective. The use of cumulative live birth rate (CLBR) per ovarian stimulation cycle is proving to be an accurate method to calculate the success of IVF; however, the cycle outcome is closely associated with the number of embryos transferred (ET). Our aim was to report CLBR after IVF according to the number of embryos required to achieve a live birth in women aged ≥35 years, considering age, body mass index (BMI), and ethnicity. Methods. We conducted a retrospective cohort study including 1344 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
7
2
Order By: Relevance
“…Further, we identified that the CLBR was significantly higher as the number of totals transferred was two. This result is different from the findings of previous research [ 58 ]. This could be due to high-quality embryos being preferentially selected for transfer, and women without obtained live birth needed to perform repeated embryo transfers.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, we identified that the CLBR was significantly higher as the number of totals transferred was two. This result is different from the findings of previous research [ 58 ]. This could be due to high-quality embryos being preferentially selected for transfer, and women without obtained live birth needed to perform repeated embryo transfers.…”
Section: Discussioncontrasting
confidence: 99%
“…Further observation revealed little difference after three cycles between conservative and optimistic CLBR. The report in the literature on CLBR was significantly different based on BMI and age; low CLBR was found with the age of ≥ 42 years and obesity 35 . In all the four groups, CLBR increased from cycle one subsequently to cycle three, meaning despite their infertility status, low prognosis women can increase their probability of conception by undergoing multiple cycles of IVF/ICSI.…”
Section: Discussionmentioning
confidence: 89%
“…It follows that, since POSEIDON criteria were introduced within the last decade, several publications have opted to assess different fertility outcomes among the four groups of low prognosis defined by the criteria 18,19 . With the majority assessing the cumulative probability of pregnancies 20,21 , a few assessed cumulative probabilities of pregnancy. However, to our knowledge, the long term perinatal and obstetric outcome is still unexplored among poor ovarian responders stratified by the criteria.…”
mentioning
confidence: 99%
“…However, In Vitro Fertilization (IVF) success remains lower than 100% and not satisfactory. Therefore, important indicators of decision making stand for the success probability and cost effectiveness as crucial to patients with a low ratio (7) . So, how to increase the favorable outcome of ART has become a critical topic for both clinicians and infertile couples.…”
Section: Introductionmentioning
confidence: 99%